DESIGN AND IMPLEMENTATION OF FIBER OPTIC INTERFEROMETER FOR PROTEIN INTERACTION ANALYSIS - Bissen, Aidana (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This capstone project particularly focuses on developing a Semidistributed Interferometer made of optic fiber, geared to protein interactions. This work consists of the design of the interferometer, calibration, and functionalization steps. This will describe data processing on the acquired data using MATLAB and study the behavior of the protein through both static and dynamic measurements. This will thus lead to very high sensitivity of the interferometer, robust methodologies of calibration, optimized techniques of functionalization, and tools in data processing that will further allow the extraction of meaningful insight from interferometer data. Ultimately, the project targets performing the studies of protein interactions using the interferometer developed in the project and hence brings out a set of cellular processes and disease mechanisms into light.
Keywords: Type of access: Open access; Fiber Optic Sensors; Interferometer; CD44 Proteins; Microfluidic Chip